2021
DOI: 10.18805/ijar.b-4556
|View full text |Cite
|
Sign up to set email alerts
|

​Impact of Dietary Aflatoxin-B1 on Juvenile Growth in White Pekin Ducks

Abstract: Background: Aflatoxicosis in ducks is reckoned as a challenge for nutritionists worldwide, for its adverse impacts on growth. A study was conducted to ascertain the precise level of Aflatoxin-tolerance in White Pekin ducklings during juvenile ages. Methods: Day-old-ducklings (240) were randomly distributed into 3 experimental-groups viz., Control ( less than 0.5 ppb), T1 (200 ppb), T2 (400 ppb) and reared for measuring weekly growth, feed efficiency and blood biochemical changes, with treatments terminated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The typical symptoms of ducklings included: ataxia, convulsions, and opisthotonos, preceding death from aflatoxicosis. Lameness, either unilateral or bilateral, as an outcome of long-term feeding of AFB1-spiked diets (@ 200 ppb for 6 weeks) to Pekin ducks was also reported [94] resulting in near condemnation of the survivor ducks as meat animals, owing to obvious reasons. The reports of Indian labs (author's own lab at ICAR-DPR) have also shown that recurrent presence of naturally arisen AFB1 (in 30-50 ppb ranges) in Pekin ducks has largely been the reason behind huge condemnation of the aflatoxicosis survivors, which not only gave rise to carcass degradation, but also affected the usual fleshing of meat-type Pekin ducks at marketable ages, say by 6-8 weeks latest [95].…”
Section: Aflatoxicosis In Ducksmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical symptoms of ducklings included: ataxia, convulsions, and opisthotonos, preceding death from aflatoxicosis. Lameness, either unilateral or bilateral, as an outcome of long-term feeding of AFB1-spiked diets (@ 200 ppb for 6 weeks) to Pekin ducks was also reported [94] resulting in near condemnation of the survivor ducks as meat animals, owing to obvious reasons. The reports of Indian labs (author's own lab at ICAR-DPR) have also shown that recurrent presence of naturally arisen AFB1 (in 30-50 ppb ranges) in Pekin ducks has largely been the reason behind huge condemnation of the aflatoxicosis survivors, which not only gave rise to carcass degradation, but also affected the usual fleshing of meat-type Pekin ducks at marketable ages, say by 6-8 weeks latest [95].…”
Section: Aflatoxicosis In Ducksmentioning
confidence: 99%
“…While other researchers [100] have cited that even feeding of 300 ppb AFB1 in Pekin duckling diets, for a period of 4 weeks, the loss in weight gain was just insignificant, the Indian studies, including that of author's own lab, have suggested that as much as 10 ppb of naturally arisen AFB1 (or higher) in duckling diets could precipitate in huge morbidity and mortalities in Pekin duck stocks. However, other authors have emphasized that mortalities to the tune of 50% of most ducklings could be witnessed in both Pekin and Khaki Campbell ducks when the naturally arisen AFB1 levels hovered around 20-41 ppb during post-monsoon periods with feeds compounded with grains stored just for 6-8 months [94]. This would mean that naturally arisen AFB1 levels were indicators of rampant and conducive growth of Aspergillus fungi, which not only produced AFB1 in locally stored feed, but also might have supported growth of other fungi, leading to co-production of other mycotoxins possibly, with possible increase of mycotoxin cocktails.…”
Section: Aflatoxicosis In Ducksmentioning
confidence: 99%
“…Generally, use of maize and groundnut is avoided in duck feed, as they are more prone to aflatoxins and ducks are very sensitive to it. Mishra et al (2021) have concluded that the AFB1 content of juvenile WP ducks should be kept limited to the recommended safe levels (<10 ppb); exceeding a threshold of 200 ppb is sure to cause poor growth and FCR, with adverse blood biochemical changes, high mortality, morbidity and lameness.…”
Section: Nutrition Of Ducksmentioning
confidence: 99%